Calculation of Temperature Distribution of Air-Cooled Three-phase dry Transformer - Bao Doan Thanh (My University, 2022)
Calculation of Temperature Distribution of Air-Cooled Three-phase dry Transformer
Keywords: Máy biến áp khô; Làm mát bằng không khí; Phân bố nhiệt